Risk Mitigation Strategy Through Analysis of Business Risk Management Implementation - Imanita Septian Rusdianti; Bagus Salam Azizi; Megawati Siliwani Putri; Rifqi Hisyam Mahendra; Rohmatul Faizah (Institut Teknologi dan Sains Mandala, 2026)
This study aims to analyze the implementation of Enterprise Risk Management (ERM) at PT Japfa Comfeed Indonesia Depo Balikpapan in identifying, evaluating, and mitigating various risks that have the potential to affect the company's operational sustainability. The study uses a descriptive case study approach with a focus on the risk management process implemented in animal feed distribution activities. The results of the study indicate that the company faces several major risks, namely operational risks in the form of delays in animal feed distribution, financial risks due to fluctuations in raw material prices, environmental risks that cause product damage due to humidity and contamination, and regulatory risks originating from changes in government policies. The implementation of ERM is carried out through five main stages, namely risk identification, risk evaluation, risk mitigation, risk monitoring, and risk review. The mitigation strategies implemented include supply chain optimization, collaboration with logistics partners, the use of a digital tracking system, humidity-based warehouse management, the implementation of the FIFO method, and strengthening coordination with suppliers and regulators. The research findings indicate that the structured implementation of ERM can improve the effectiveness of risk control, maintain product quality, reduce potential operational and financial losses, and strengthen the company's business resilience. Therefore, ERM is an important instrument in supporting the company's operational sustainability and competitiveness in the dynamic animal feed industry.